2019
DOI: 10.1002/brb3.1225
|View full text |Cite
|
Sign up to set email alerts
|

The effects of perinatal bisphenol A exposure on thyroid hormone homeostasis and glucose metabolism in the prefrontal cortex and hippocampus of rats

Abstract: Introduction Bisphenol A (BPA) is an endocrine disruptor widely used to manufacture consumer goods. Although the thyroid hormone (TH) disrupting potential of BPA has been thought to be responsible for the neuropsychiatric deficits in the animals that experienced perinatal BPA exposure, the TH availability change at the level of specific brain structures has not been subject to systematic investigation. Methods In the present study the impacts of perinatal BPA exposure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 72 publications
(102 reference statements)
3
8
0
Order By: Relevance
“…Two studies have investigated the relationship of BPA exposure with thyroid function (Table 3). Viguié et al [122] reported that BPA exposure of pregnant ewes was associated with a transitory hypothyroxinemia of both mothers and their newborn lambs, with a significant reduction of both circulating total T4 (TT4) and free T4 (FT4), findings in agreement with rodent studies [111,112]. In a following study, the authors confirmed alterations of gestational thyroid function, observing a significant reduction of FT4 and total T3 (TT3), but not TT4, in pregnant ewes treated with environmentally-relevant BPA concentrations via subcutaneous and dietary routes of administration [123].…”
Section: Sheepsupporting
confidence: 57%
See 2 more Smart Citations
“…Two studies have investigated the relationship of BPA exposure with thyroid function (Table 3). Viguié et al [122] reported that BPA exposure of pregnant ewes was associated with a transitory hypothyroxinemia of both mothers and their newborn lambs, with a significant reduction of both circulating total T4 (TT4) and free T4 (FT4), findings in agreement with rodent studies [111,112]. In a following study, the authors confirmed alterations of gestational thyroid function, observing a significant reduction of FT4 and total T3 (TT3), but not TT4, in pregnant ewes treated with environmentally-relevant BPA concentrations via subcutaneous and dietary routes of administration [123].…”
Section: Sheepsupporting
confidence: 57%
“…In other experiments, BPA exposure did not produce significant variations in plasma T4 levels [106][107][108][109] or, alternatively, the effects may not endure after BPA removal and metabolism [110][111][112]. It is still unclear whether exposure to BPA and its derivatives can cause hypothyroidism due to limited evidence.…”
Section: Rodentsmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, recent interests are being directed to the effects of these substances on the thyroid tissue and thyroid hormone regulation, linking the changes in thyroid function with the consequential adverse reproductive health [35,36]. To investigate the effects of phthalates on the thyroid, in vivo rodent studies have been conducted to reveal the decrease in thyroid hormones after oral exposure to DEHP [35,37,38], DBP [39], and BPA [40,41]. This is in accordance with the human biomonitoring study from the national health and nutrition examination survey (NHANES, 2007(NHANES, -2008, which included 1346 adults (ages ≥20 years) and 329 adolescents (ages 12-19 years).…”
Section: Introductionmentioning
confidence: 99%
“…BPA is a good illustration on how a contaminant that does not seem to have any effect on the thyroid function of adult non-pregnant animals might affect this function in pregnant animals and/or their offspring. There are indeed data in both rodents and sheep showing that BPA can alter the thyroid function of pregnant animals and/or their offspring (Guignard et al, 2017;Silva et al, 2019;Viguié et al, 2013;Xu et al, 2019;Zoeller et al, 2005).…”
mentioning
confidence: 99%